Penerapan Asas Legalitas terhadap Hukum yang Hidup dalam Masyarakat (Living Law) Menurut Undang-Undang Nomor 1 Tahun 2023 tentang KUHP - Dawarman, Dawarman; Laia, Aturkian (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The enactment of Law No. 1 of 2023 on the Criminal Code sparks academic debate as it simultaneously maintains the principle of formal legality and recognizes the living law (living law) as a basis for criminal liability. This normative legal research, employing statute, conceptual, and historical approaches, aims to examine the conceptual consistency between these two principles and its implications for legal certainty. The results indicate that the living law is formulated as a form of extended legality (extended legality). Its application is contingent upon procedural requirements via local regulations and substantive requirements regarding compatibility with Pancasila, the 1945 Constitution, and human rights. Despite its official recognition, the unwritten and particularistic nature of customary law still poses potential tensions with the principle of legal certainty and risks causing disparities in court rulings across regions. This study recommends the careful drafting of technical guidelines for local regulations to bridge legal pluralism with the protection of citizens’ rights.